2017
DOI: 10.1371/journal.pone.0180505
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis to identify vaccine candidates common to multiple serotypes of Shigella and evaluation of their immunogenicity

Abstract: Shigellosis or bacillary dysentery is an important cause of diarrhea, with the majority of the cases occurring in developing countries. Considering the high disease burden, increasing antibiotic resistance, serotype-specific immunity and the post-infectious sequelae associated with shigellosis, there is a pressing need of an effective vaccine against multiple serotypes of the pathogen. In the present study, we used bio-informatics approach to identify antigens shared among multiple serotypes of Shigella spp. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Since the experimental methods are difficult and time-consuming, the immuno-informatics approach can narrow down a vast number of potential molecules to be tested, thus increasing the chance of finding better candidates. Numerous studies have shown that epitopes based vaccines could be effective in elucidating protective immunity against various pathogens such as influenza A, hepatitis B and C virus, Leishmania and Shigella ( 28 32 ). In this study, using immuno-informatics-driven vaccine target screening strategy, the available transcriptomic and proteomic data for Theileria parasites were analyzed to predict proteins/epitopes for vaccine development that could elicit protective humoral and cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Since the experimental methods are difficult and time-consuming, the immuno-informatics approach can narrow down a vast number of potential molecules to be tested, thus increasing the chance of finding better candidates. Numerous studies have shown that epitopes based vaccines could be effective in elucidating protective immunity against various pathogens such as influenza A, hepatitis B and C virus, Leishmania and Shigella ( 28 32 ). In this study, using immuno-informatics-driven vaccine target screening strategy, the available transcriptomic and proteomic data for Theileria parasites were analyzed to predict proteins/epitopes for vaccine development that could elicit protective humoral and cellular immune response.…”
Section: Introductionmentioning
confidence: 99%
“…The validity and benefits of peptide vaccines designed by bioinformatics tools had been verified by appreciable research [24]. The availability of the complete genome, proteome sequences, and pathogenesis of many pathogenic microorganisms contributed to the production of a vaccine through bioinformatics [24, 39]. In this study, the predicted epitopes from B and T lymphocytes would help in the development of a more effective, reliable, preventive, and therapeutic vaccine against the PPRV than the conventional methods.…”
Section: Resultsmentioning
confidence: 93%
“…Linear B-cell epitopes prediction tools generated better accuracy than the discontinuous B-cell epitopes prediction. Several studies even only used linear B-cell tools for the prediction for the epitopes [46,55,56]. Entropy method (ExPaSy) was one way to determine the conserved residues.…”
Section: Nattokinase Antigenicity and B-cell Epitopes Determinationmentioning
confidence: 99%